2019
DOI: 10.25259/sni_102_2019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of forced-air warming blanket position in elective lumbar spine surgery: Intraoperative body temperature and postoperative complications

Abstract: Background:Perioperative hypothermia is linked to multiple postoperative complications including increased surgical bleeding, surgical site infection, myocardial events, and increased length of hospital stay. The purpose of this study is to determine the effects of forced-air warming blanket position, above the shoulders versus under the trunk/legs, on intraoperative core body temperature and perioperative complications in elective lumbar spine surgery.Methods:After IRB approval, patients were enrolled in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Nevertheless, the previous studies found that the risk factors affecting intraoperative hypothermia in surgical patients mainly included age, BMI, heat preservation measures, laboratory indicators and surgery‐related factors (Buraimoh et al, 2019; Wagner et al, 2021b; Yi et al,2018b). In addition, types of anaesthesia and surgery and smoking also affected body temperature adjustment, causing a lower postoperative body temperature (Takashima et al, 2019; Schälte et al, 2010; Vanderstocken et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the previous studies found that the risk factors affecting intraoperative hypothermia in surgical patients mainly included age, BMI, heat preservation measures, laboratory indicators and surgery‐related factors (Buraimoh et al, 2019; Wagner et al, 2021b; Yi et al,2018b). In addition, types of anaesthesia and surgery and smoking also affected body temperature adjustment, causing a lower postoperative body temperature (Takashima et al, 2019; Schälte et al, 2010; Vanderstocken et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, on the one hand, these models were mainly for the prediction of intraoperative hypothermia, and less attention was paid to postoperative hypothermia. On the other hand, most prediction (Buraimoh et al, 2019;Wagner et al, 2021b;Yi et al,2018b). In addition, types of anaesthesia and surgery and smoking also affected body temperature adjustment, causing a lower postoperative body temperature (Takashima et al, 2019;Schälte et al, 2010;Vanderstocken et al, 2020).…”
Section: Discussionsmentioning
confidence: 99%
“…One study reported on the differences between upper- and lower-body blanket warming during spine surgery in the prone position. Buraimoh et al [ 12 ] reported no difference in warming efficacy between upper- and lower-body blankets in patients undergoing spine surgery. In their study, the incidence rates of severe hypothermia (< 35°C) and mild to moderate hypothermia (35–36°C) in the upper-warming group were similar to those in our study (18.4% and 34.2%, respectively), but the rates of severe and mild to moderate hypothermia in the lower-warming group were lower than our rates (11.1% and 30.6%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…According to a preliminary retrospective study conducted at our institution, upper-body warming results in a significantly lower incidence of hypothermia compared with lower-body warming, during spine surgery in the prone position (unpublished data). However, few studies have compared the effectiveness of upper- and lower-body warming during spine surgery in the prone position [ 12 ]. We hypothesized that an upper-body blanket would be superior to a lower-body blanket to prevent perioperative hypothermia in patients undergoing spine surgery in the prone position.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that the FAW system is superior to passive insulation and any other active warming methods in preventing IPH of surgical patients [7,13] . Although FAW is an effective method to combat IPH, its effects may be affected by the FAW blanket style and position [14,15] . During arthroscopic shoulder surgery, as during any other surgeries that require special surgical positioning of patients, anesthesiologists and operating room nurses prefer to place the FAW blanket under the patient's body rather than over it because of the ease of setup and management.…”
Section: Introductionmentioning
confidence: 99%